Persuasive Communication Of The Information And Counseling Customer Complaints Unit At DR. M. Yunus Hospital Bengkulu On Patients’ Problems (Case Study at M. Yunus Bengkulu Hospital) - Rama Diansyah; Anis Endang; Bayu Risdiyanto (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the persuasive communication of the Information and Counseling Customer Complaints Unit at RSUD Dr. M Yunus Bengkulu. This study used qualitative research with data collection techniques, namely observation, interviews, and documentation. The theoretical basis used was the concept of persuasive communication according to De Vito (2011: 120), namely the nature that strengthens, provides illustrations, and offers information. The results of the study show that first, Reinforcing Properties; Persuasive communication applied by UPPIK to patients. Characteristics that can be strengthened include mutual respect and acceptance of differences in various matters as a good thing, tolerance for their different interests and carrying out joint activities in a community environment. Second, Providing Illustrations; Shown by the patient The use of illustrations will make it easier for the message/explanation to be understood by the patient. Third, Presenting Information; Presenting information in a persuasive manner refers to the message (speech or expression) that the UPPIK officer wants the patient to record or transmit from the message conveyed. Thus, it can be concluded that UPPIK officers apply mutual respect and make it easier to convey messages so that they form a character that strengthens, provides illustrations, and provides information in solving patients’ problems.